Development and Evaluation of Centralized Collection and Delivery System of New Canaan Insurance Agency, Inc. - Ambre, Janelyn (JPAIR Multidisciplinary Research, 2016)
The use of information technology at present is considered as one of the solutions for business establishments for their expense and quality issues. It is their key to staying ahead of their competitors. The study is intended to trace and monitor the transactions of the New Canaan Insurance Agency, Inc. (NCIA) involving collection, payment, delivery, and pick-up. It also monitored the performance of the liaison officers and the request of transaction is centralized. The researcher developed the Centralized Collection and Delivery System (CCDS) of New Canaan Insurance Agency, Inc (NCIA). The descriptive and applied types of research were employed in the study. Data were gathered through interview and feedback form. The respondents were from the 28 employees of NCIA. The Evolutionary Prototype model was used in the development of the system and the USE questionnaire to test its usability. The gathered data were analyzed and interpreted using frequency count and mean. Findings revealed that the procedures on collection, delivery, payment, and pick-up start with an employee's request forwarded to the liaison officers which is done manually. Using the Evolutionary Prototype Model, the Centralized Collection and Delivery System was developed. The developed system was found to be efficient because it was designed to fit the needs of NCIA.
Keywords: Information Technology; centralized collection and delivery system; ease of use; ease of learning; evolutionary prototype model; descriptive design; and Makati City; Philippines